Roots of Traditional Islamic Thought in Indonesia: Paradigms and Key Figures in Pesantren Education - Fitrotul Maulidina; Mubaraq, Zulfi (Pesantren and Community Development Studies - Islamic Institute of Syarifuddin, Indonesia., 2025)
This study examines the roots of traditional Islamic thought in Indonesia with a focus on the paradigm, influencing factors, and educational implications of Islamic boarding schools (pesantren). Previous studies have often been limited to historical, biographical, or conceptual approaches, resulting in partial understandings. To address this gap, the present research employs a systematic literature review (SLR) with a qualitative approach. Data were collected from 30 peer-reviewed national journal articles published between 2015–2025, selected through a three-stage process of identification, screening, and eligibility. Analysis was conducted using Harold Lasswell’s content analysis framework to categorize findings into three main clusters. The results reveal three dominant paradigms of traditional Islamic thought: conservative, modernist, and pragmatic. The development of these paradigms is shaped by internal factors including pesantren knowledge, kyai spirituality, and local customary values and external factors such as social change, technology, and politics. The implications are twofold: positively, traditional Islamic thought contributes to civilization, inclusiveness, and educational transformation; negatively, it presents challenges such as resistance to change, interpretative conflicts, and unequal access. This study contributes to the scholarship on Indonesian Islamic education by offering a comprehensive synthesis of pesantren’s role as both a preserver of tradition and an agent of adaptation in modern society. The findings highlight the need for pesantren to develop hybrid models that integrate classical learning with contemporary educational practices, ensuring their continued relevance in the global context.